2020
DOI: 10.3390/antiox9121288
|View full text |Cite
|
Sign up to set email alerts
|

The Writers, Readers, and Erasers in Redox Regulation of GAPDH

Abstract: Glyceraldehyde 3–phosphate dehydrogenase (GAPDH) is a key glycolytic enzyme, which is crucial for the breakdown of glucose to provide cellular energy. Over the past decade, GAPDH has been reported to be one of the most prominent cellular targets of post-translational modifications (PTMs), which divert GAPDH toward different non-glycolytic functions. Hence, it is termed a moonlighting protein. During metabolic and oxidative stress, GAPDH is a target of different oxidative PTMs (oxPTM), e.g., sulfenylation, S-th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 155 publications
0
38
0
Order By: Relevance
“…On the contrary, DNA-activated protein kinase (DNA-PK), which is involved in DNA repair, is activated by S-nitrosylation with the participation of GAPDH-SNO [88,97]. In response to stress, GAPDH is translocated into the mitochondria, where it transnitrosylates Hsp60, acetyl-CoA thiolase, and VDAC1, thus affecting membrane permeability, the regulation of mitochondrial function, and cell death [98,99].…”
Section: Protein S-nitrosylation and Denitrosylationmentioning
confidence: 99%
“…On the contrary, DNA-activated protein kinase (DNA-PK), which is involved in DNA repair, is activated by S-nitrosylation with the participation of GAPDH-SNO [88,97]. In response to stress, GAPDH is translocated into the mitochondria, where it transnitrosylates Hsp60, acetyl-CoA thiolase, and VDAC1, thus affecting membrane permeability, the regulation of mitochondrial function, and cell death [98,99].…”
Section: Protein S-nitrosylation and Denitrosylationmentioning
confidence: 99%
“…A previous study on reference genes for rat mesangial cells found ACTB to be one of the best reference genes for this cell line under high glucose conditions, in conformity with our findings [ 17 ]. Glyceraldehyde 3-phosphate dehydrogenase ( GAPDH ), although it is reported to be involved in cellular survival, apoptosis and DNA repair, is mainly known to express a cellular energy enzyme determinant of the glycolytic process, functioning as a catalyzer of triose phosphate oxidation and, for this reason, ubiquitously distributed in all cell types [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, over 2200 CoAlated proteins have been identified in prokaryotic and eukaryotic cells exposed to oxidative or metabolic stress. Protein CoAlation has been shown to regulate the activity and subcellular localization of modified proteins, protect oxidized cysteine residues from irreversible overoxidation, and to induce conformational changes (Gout, 2018(Gout, , 2019Bakovic et al, 2019;Tossounian et al, 2020;Tsuchiya et al, 2020;Yu et al, 2021). The antioxidant function of CoA and protein CoAlation in pathologies associated with oxidative stress, such as neurodegeneration, cancer, and diabetes, remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%